Hubungan antara Kepatuhan Ibu Hamil Mengkonsumsi Tablet Fe, Asupan Fe, Protein dan Vitamin C dengan Kejadian Anemia di Puskesmas Kalasan - Arum Dyah Ratnasari; I Made Alit Gunawan; Abidillah Mursyid (Poltekkes Kemenkes Yogyakarta, 2017)
Background : Iron deficiency anemia is one of the most common disorders that occur during pregnancy. Factors affecting anemia there is a wide range between low intake of other nutrients (intake of protein, iron, and vitamin C). Besides the low compliance of pregnant women in consuming iron tablet is one of the causes of the prevalence of anemia remains high. Data from health center Kalasan shows the percentage of anemia in pregnant mothers in 2015 by 22%. Objective : This study aims to determine the relationship between compliance of pregnant women consume iron tablet, intake of iron, protein and vitamin C with anemia in health center Kalasan. Methods : The study was conducted using cross sectional design in health center Kalasan in September through November 2016. The sample is third trimester pregnant women who totaled 41 people who meet the criteria for inclusion and exclusion. Samples were taken by way of Systematic Random Sampling. Data collected from mothers consuming compliance iron iron tablet, intake of iron, protein, vitamin C and anemia status. The data obtained in the test statistic used in the bivariate analysis were Chi Square test. Result : After analyzed the results get most expectant mothers dutifully consume the iron tablet (70.7%), iron intake in good (65.9%), protein intake in good (68.3%), vitamin C intake in good (65.9%) and anemia (70.7%). Conclusion : There is relationship compliance pregnant women consume iron tablets with anemia, there is a relationship iron intake with the incidence of anemia, there is a relationship of protein intake with the incidence of anemia, and no association of vitamin C intake with the incidence of anemia. Keywords: Compliance rate, Iron tablets, Iron intake, Protein, Vitamin C, Anemia